Segmental intestinal reconfiguration (SIR) in combined reconstructions for ultrashort bowel syndrome - Vasily V. Nikolaev; Julia Averyanova (Elsevier, 2024)
Background: Ultrashort bowel syndrome represents the most rare and complex variant of the short bowel syndrome. Autologous intestinal reconstructions for ultrashort bowel syndrome is typically reserved for severe cases characterized by symptomatic dysmotility within the ultrashort dilated segments. Limited surgical techniques are available to substantially increase the length of ultrashort bowels with asymmetric and highly dilated segments.We present a case series detailing the application of a technique for lengthening and tapering significantly dilated ultrashort bowels - segmental intestinal reconfiguration (SIR), based on the Yang-Monti principle. Our analysis delves into the technical features across various anatomical variants and provides mid-term results. Methods: From 2021 to 2022, patients experiencing dysmotility in dilated ultrashort bowel segments with a preserved colon underwent sequential combined intestinal reconstructions. Assessments were conducted 18-24 months post-surgery, and statistical calculations employed nonparametric methods to compare pre- and postoperative results. Results: Six patients, with a median age of 48.5 months, underwent autologous intestinal reconstructions, including SIR. The serial transverse enteroplasty (STEP) was performed on the dilated duodenum in five children, and colon interposition in two. The length of the small bowel exhibited a significant difference before and after surgery (p = 0.031). No complications were observed in the postoperative period. The postoperative group demonstrated a lower dependence on parenteral nutrition (NPEI/REE < 80 % in 6 (100.0 %); p = 0.007). Enteral autonomy was restored in two children. Conclusions: The results of SIR technique in combined reconstructions for ultrashort bowel syndrome in a carefully selected cohort of children demonstrate feasibility and reliability, as well as the restoration of intestinal transport function at midterm evaluation. This comprehensive approach resulted in increased enteral tolerance and reduced parenteral requirements.